Suture stabilization of the acromioclavicular ligament plus clavicular hook plate fixation vs. total ligament repair with loop plates for acromioclavicular joint dislocation - Gang Ren; Xiaowen Huang (Journal of Orthopaedic Surgery and Research)
Abstract Objective The aim of this study is to compare the clinical efficacy of suture stabilization of the acromioclavicular (AC) ligament plus clavicular hook plate fixation vs. total ligament repair with loop plates for treating AC joint dislocation. Methods Sixty-five patients who were admitted to Department of Orthopedics at Jiangsu Provincial People’s Hospital (First Affiliated Hospital of Nanjing Medical University) and Capital Center for Children’s Hospital, Capital Medical University for AC joint dislocation from January 2021 to June 2023, and satisfied the inclusion and exclusion criteria, were reviewed retrospectively. These patients were divided into Group A and Group B. There were 34 patients in Group A (study group), including 22 males and 12 females with an average age of 42.1 ± 6.8 years old. They received suture stabilization of the AC ligament combined with clavicular hook plate fixation. There were 31 patients in Group B (control group), including 20 males and 11 females with an average age of 41.6 ± 7.5 years old. They received total ligament repair using Endobutton loop plates, which consisted of anatomical double-bundle reconstruction of the CC ligaments and anatomical single-bundle reconstruction of the AC ligament. The two groups were compared in terms of general surgical parameters, hospitalization parameters, complications, reduction degree, imaging parameters, and Constant-Murley Score for Shoulder Function. Results All patients were followed up for 6 to 16 months, with an average of 9.7 months. Group A outperformed Group B significantly in several parameters, including the operation time, incision length, intraoperative blood loss, length of hospital stay, and hospitalization costs (P < 0.05). Group A also outperformed Group B significantly in the reduction degree (P < 0.05). As for the Constant-Murley Score for Shoulder Function, the two groups did not differ significantly before surgery or at 6 months after surgery (P > 0.05). However, Group A outperformed Group B significantly in the Constant-Murley Score for Shoulder Function after the removal of internal fixation (P < 0.05). The two groups did not differ significantly in the incidence of complications or imaging parameters (P > 0.05). Conclusion Suture stabilization of the acromioclavicular ligament combined with clavicular hook plate fixation achieved satisfactory elastic and rigid fixation concurrently in AC joint dislocation, increasing AC joint stability in all directions. Besides, this procedure significantly decreased the stress load acting around the AC joint, which further decreased the complications. Suture stabilization of the ligaments combined with clavicular hook plate fixation was conducive to restoring shoulder functions, and had a higher economic efficiency. This surgical procedure deserves special attention.